Hard Lessons from South Sudan. Issue 5 (3rd September 2021) - Berdal, Mats; Shearer, David
Abstract: South Sudan's tragic history of independent statehood raises important questions about the future of the United Nations Mission in South Sudan (UNMISS). UNMISS cannot bring peace to the country on its own. For that to happen, South Sudan's militarised form of governance and political economy must be transformed. Recognising UNMISS's limitations does not, however, preclude a vital and continuing role for the mission. UNMISS must work to reduce alarming levels of local and sub-national violence and help shore up the fragile peace agreement reached between Salva Kiir and Riek Machar in 2018. The mission must also manage the risks of further instability posed by poorly managed security-sector reform and elections scheduled for 2022. Finally, UNMISS and the UN must intensify the search for political avenues out of violence. To this end, renewed and constructive international engagement must be marshalled, and the UN must absorb important lessons from its own performance.